A Statistical Analysis of Attitudinal Changes Towards Female Breadwinners in Wukari Local Government Area - Mathew, Stephen; Idi, Danjuma; Dangana, Blessing (Lembaga Yasin AlSys, 2024)
This study carried out a statistical analysis of attitudinal changes towards female breadwinners in Wukari Local Government Area, Taraba State, Nigeria. Using a survey research method, a sample of 400 were examined. Primary data were collected using structured questionnaire and analysed using frequency counts and simple percent. Hypothesis were tested using the chi-square statistic. The findings reveal that a significant proportion of respondents recognize the importance of defining roles and responsibilities within the family, acknowledging the potential impact of female breadwinners on traditional family structures. Additionally, a notable portion of respondents agree that female breadwinners face financial and other challenges. Also, the findings reveal a significant shift in gender roles, driven by economic opportunities, social dynamics, and cultural norms. Hypothesis testing further demonstrates a significant increase in female breadwinners in the area, attributed to economic, social, and cultural factors. The study concludes by emphasizing the need for understanding and recommends awareness programs, policy interventions, educational initiatives in Wukari LGA.